The Impact of Mobile Phone on Family Life: A Case Study of Lahore, Pakistan - sarwar, shabbir; Humara Gulzar; Muhammad Ahsan Bhatti (Journal of Peace, Development and Communication, 2021)
The purpose of this research paper is to explore the negative relationship between mobile phone and family life as well as negative impact of mobile phone usage on family life norms and traditions. The study is based on data collected through mixed method i.e. survey of a random sample of 1300 people and structured interviews conducted with a sub-sample of 13 people in Lahore, Pakistan. The study found that mobile phone is negatively affecting the family life due to its massive usage during family socialization time. The quantitative analysis found that over 85% of respondents use mobile phone for communication with the people other than their family members when they are with their family; over 50% make calls to others during their family time; 83% make SMS; 75 feel that they ignore their family due to cell phone; 86% thinks that mobile has influenced their family time face-to-face socialization negatively and 91% said that they exchanged harsh words with their family members for at least once or more due to using mobile phone during family time. The study reveals that male members of the traditional families are more responsible for using mobile phone during family time and damaging family traditions as compared to the female members. However, parents remain very concerned about the possibilities of misuse of mobile phone by female teenagers of the family. In most cases family elders were annoyed with the youth for adopting this change in their behaviors damaging the family traditions.